Dissecting the basis for differential substrate specificity of ADAR1 and ADAR2 - Marlon S. Zambrano-Mila; Monika Witzenberger; Zohar Rosenwasser; Anna Uzonyi; Ronit Nir; Shay Ben-Aroya; Erez Y. Levanon; Schraga Schwartz (Nature Communications, 2023)
Abstract Millions of adenosines are deaminated throughout the transcriptome by ADAR1 and/or ADAR2 at varying levels, raising the question of what are the determinants guiding substrate specificity and how these differ between the two enzymes. We monitor how secondary structure modulates ADAR2 vs ADAR1 substrate selectivity, on the basis of systematic probing of thousands of synthetic sequences transfected into cell lines expressing exclusively ADAR1 or ADAR2. Both enzymes induce symmetric, strand-specific editing, yet with distinct offsets with respect to structural disruptions: −26 nt for ADAR2 and −35 nt for ADAR1. We unravel the basis for these differences in offsets through mutants, domain-swaps, and ADAR homologs, and find it to be encoded by the differential RNA binding domain (RBD) architecture. Finally, we demonstrate that this offset-enhanced editing can allow an improved design of ADAR2-recruiting therapeutics, with proof-of-concept experiments demonstrating increased on-target and potentially decreased off-target editing.